Truth, good and beauty: the politics of celebrity in China - Sullivan, Jonathan; Kehoe, Séagh (Cambridge University Press, 2017)
A visit to a Chinese city of any size—looking up at downtown billboards, riding public transport, shopping at a mall—is to be in the presence of a Chinese celebrity endorsing a product, lifestyle or other symbols of “the good life”. Celebrity in China is big business, feeding off and nourishing the advertising-led business model that underpins the commercialized media system and internet. It is also a powerful instrument in the Party-State’s discursive and symbolic repertoire, used to promote regime goals and solidify new governmentalities through signalling accepted modes of behaviour for mass emulation. The multi-dimensional celebrity persona, and the public interest it stimulates in off-stage lives, requires an academic focus on the workings of celebrity separate to the products that celebrities create in their professional roles. The potential to connect with large numbers of ordinary people, and the emergence of an informal celebrity-making scene in cyberspace symptomatic of changing attitudes towards fame among Chinese people, marks the special status of celebrity within China’s constrained socio-political ecology. The motivation for this article is to further scholarly understanding of how celebrity operates in China and to bring this expression of popular culture into the broader conversation about contemporary Chinese politics and society.